2015
DOI: 10.1093/rheumatology/kev270
|View full text |Cite
|
Sign up to set email alerts
|

High systemic levels of low-density lipoprotein cholesterol: fuel to the flames in inflammatory osteoarthritis?

Abstract: There is increasing evidence that low-density lipoprotein (LDL) cholesterol plays a role in the pathology of OA. Specifically, oxidized LDL (oxLDL), which has been shown to play an essential role during development of atherosclerosis, could be involved in processes such as synovial inflammation, cartilage destruction and bone deformations. OxLDL can activate synovial cells such as macrophages, endothelial cells and synovial fibroblasts, resulting in release of growth factors, MMP and pro-inflammatory cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 95 publications
0
51
0
1
Order By: Relevance
“…Again, this advocates a role for inflammation in OA development, as previously argued for the hCRP strain. For OA patients the benefit of statin therapy is unclear at present, as human studies investigating the effect of statins on OA development are scarce and a beneficial effect is not observed in all studies 55 . Potential beneficial effects might however be missed due to underdosing, as we have previously shown that the optimal lipid-lowering statin dose is much lower than the threshold for the anti-inflammatory effects 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Again, this advocates a role for inflammation in OA development, as previously argued for the hCRP strain. For OA patients the benefit of statin therapy is unclear at present, as human studies investigating the effect of statins on OA development are scarce and a beneficial effect is not observed in all studies 55 . Potential beneficial effects might however be missed due to underdosing, as we have previously shown that the optimal lipid-lowering statin dose is much lower than the threshold for the anti-inflammatory effects 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cholesterol accumulation in the cartilage can impair the efflux function of cartilage, hence inducing OA [27, 28]. Oxidized LDL can activate synovial cells such as macrophages, endothelial cells, and synovial fibroblasts, resulting in release of growth factors, MMP, and proinflammatory cytokines, causing cartilage destruction and bone deformations [29]. …”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence suggesting that dyslipidemia, and particularly high oxidized LDL-cholesterol, has a role in osteoarthritis pathology independent of obesity and mechanical overload 7477 . The hip, knee and hand joints may have different susceptibility to metabolic and non-metabolic factors 78,79 .…”
Section: Comorbiditiesmentioning
confidence: 99%